Patient’s intellectual and memory impairments before and after resection of brain glioma - V. Yu. Cherebillo; M. Yu. Kurnukhina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
The objective of the study was the analysis and evaluation of patients` intellectual and memory impairments before and after resection of brain gliomaMaterial and methods. We performed the study of 30 patients with brain glioma. The diagnosis of the studied patients was based on clinical and laboratory data, data of radiation and instrumental methods of research. The analysis of patients` intellectual and memory impairments was carried out in the preoperative and early, late postoperative periods. The patients` age ranged from 25 to 65 years; the median age was 56.5 year. In the present study, we used the following tests: intelligence tests – Amthauer test (for persons under 60 years), Raven test; memory tests – 10 word memorization test, Wechsler memory scale.Results. We revealed regression of various memory (from 100 to 96.7 %) and intellectual disorders (from 20 to 3.3 %; p<0.05). Short-term memory in patients with brain glioma revealed more pronounced changes in comparison with long-term memory disorders after surgery. Improvement of verbal and logical memory, visual and associative memory after surgical treatment was found. In the late postoperative period, there was an increase in the intelligence coefficient (p<0.05), a decrease in the number of patients with severe dementia (from 16.7 to 3.3 %) and an average intelligence level (from 30 to 13.3 %) (p<0,05). Conclusion. The study revealed that surgery led to regression of intellectual and memory disorders in patients with brain glioma.